TEORI SELF CARE DARI OREM: FILOSOFI DAN PRAKTEK DALAM KEPERAWATAN - Desi Fitriyanti; Siti Rahmalia (LPPM Universitas Abdurrab, 2026)
This literature review analyzes the philosophy and practical applications of Dorothea Orem's Self-Care Theory within the context of contemporary nursing, addressing implementation challenges. Data were collected from scholarly articles, books, and journals published between 2010 and 2025, accessed through PubMed, Google Scholar, and ScienceDirect. The analysis reveals that Orem's theory, grounded in three core concepts—self-care (the patient's independence in meeting basic needs), self-care deficit (the inability to care for oneself due to illness/injury), and the nursing system (nurse support according to the level of dependence)—emphasizes patient autonomy and a holistic approach. In practice, this theory guides nurses in identifying self-care deficits, designing personalized interventions, and empowering patients through health education. However, implementing this theory faces various challenges, such as low patient health literacy, limited nursing time, cultural barriers, and healthcare infrastructure constraints. Conversely, technological advancements like digital health applications, telemedicine, and multidisciplinary collaboration present new opportunities to enhance the theory's effectiveness. Case studies involving patients with chronic illnesses demonstrate that applying Orem's theory can improve health outcomes, such as medication adherence and reduced complications. Therefore, strategic adaptations are necessary. These include patient-centered communication training for nurses, integrating digital technology into care, and policy support for community-based health empowerment. Future research is recommended to develop hybrid models that combine Orem's theoretical principles with technological innovations to improve the accessibility and scalability of self-care interventions.